The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1039/c9ra10775d
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, magnetic, optical and thermoelectric properties of Ca2Cr1−xNixOsO6 double perovskites

Abstract: With the help of density functional theory calculations, we explored the recently synthesized double perovskite material Ca2CrOsO6 and found it to be a ferrimagnetic insulator with a band gap of ∼0.6 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 74 publications
(71 reference statements)
0
18
0
Order By: Relevance
“…The thermoelectric performance of a material is given by dimensionless parameter known as figure of merit (ZT) given by ZT ¼ S 2 σT k e þk l ð Þ , where S, σ, T, k e , and k l represent the Seebeck coefficient, electrical conductivity, temperature, electrical thermal conductivity, and lattice thermal conductivity, respectively. 45 A material with ZT value close to unity is considered to be good thermoelectric material. The high ZT value can only be obtained when there is a ultra-low thermal conductivity and high electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The thermoelectric performance of a material is given by dimensionless parameter known as figure of merit (ZT) given by ZT ¼ S 2 σT k e þk l ð Þ , where S, σ, T, k e , and k l represent the Seebeck coefficient, electrical conductivity, temperature, electrical thermal conductivity, and lattice thermal conductivity, respectively. 45 A material with ZT value close to unity is considered to be good thermoelectric material. The high ZT value can only be obtained when there is a ultra-low thermal conductivity and high electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Since both optical and transport properties of bandgap materials are central to determining their utilization in solar radiation‐based devices, it is intuitive to examine these properties simultaneously. For instance, Bhandari et al 22 studied Ca 2 Cr 1‐x Ni x OsO 6 double perovskites to study their electronic and magnetic characteristics along with optical and thermoelectric traits using density functional theory (DFT). The results revealed that the prepared double perovskite was ferrimagnetic with a small bandgap (eg, ~0.6 eV) and is optically isotropic.…”
Section: Introductionmentioning
confidence: 99%
“…As it is experimentally and theoretically established that DPOs are considered beneficial candidates for electron and hole-doping at A or B site, aiming to obtain optimized physical properties that were not present in their undoped form 31 47 . For example, in a widely studied DPO, electron doping which is obtained by partial replacement of with results in the enhancement of 31 34 .…”
Section: Introductionmentioning
confidence: 99%
“…It is also predicted that extra electrons go to the Mo 4 d orbitals, which are responsible for metallicity in these doped systems. Very recently, Bhandari et al 47 , theoretically demonstrated that electron doping at B site (i.e., 50% Ni-doping at Cr site) in a FiM Mott-insulator gives rise to a nearly compensated HM state which has potential applications for spintronic devices. In this case, Ni is in a 2 state with configurations and when it is replaced with Cr of charge of having a configuration of , therefore, five extra electrons added to the system which results in an HM state.…”
Section: Introductionmentioning
confidence: 99%